Pengaruh Work-Life Balance dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Generasi Z dan Peran Mediasi Keterikatan Kerja (Studi pada PT Torabika Eka Semesta Tangerang Banten) - Nila Apriliyanti; Abdul Kodir Djaelani; Ahmad Subhan Mahardani (UNIVERSITAS ISLAM MALANG, 2026)
Abstract Gen Z workers at PT Torabika Eka Semesta were the subjects of this research, which aimed to determine the relationship between work-life balance, workplace climate, and job satisfaction via the medium of work engagement. Researchers used purposive random sampling to gather data from 93 respondents using quantitative methodologies. Structural Equation Modeling (SEM) analysis based on PLS was then used to analyze the data. According to the findings, job satisfaction and engagement were positively affected by both work-life balance and the work environment. Curiously, although work engagement did moderate the link between work environment and job satisfaction, it did not significantly mitigate the effect of work-life balance on job satisfaction. Keywords: Work-Life Balance, Work Environment, Job Satisfaction, Work Engagement, Generation Z.